Hormonal control of inflammatory responses - J. Garcia-Leme; Sandra P. Farsky (Mediators of Inflammation)
Almost any stage of inflammatory and immunological responses is affected by hormone actions. This provides the basis for the suggestion that hormones act as modulators of the host reaction against trauma and infection. Specific hormone receptors are detected in the reactive structures in inflamed areas and binding of hormone molecules to such receptors results in the generation of signals that influence cell functions relevant for the development of inflammatory responses. Diversity of hormonal functions accounts for recognized pro- and anti-inflammatory effects exerted by these substances. Most hormone systems are capable of influencing inflammatory events. Insulin and glucocorticoids, however, exert direct regulatory effects at concentrations usually found in plasma. Insulin is endowed with facilitatory actions on vascular reactivity to inflammatory mediators and inflammatory cell functions. Increased concentrations of circulating glucocorticoids at the early stages of inflammation results in downregulation of inflammatory responses. Oestrogens markedly reduce the response to injury in a variety of experimental models. Glucagon and thyroid hormones exert indirect anti-inflammatory effects mediated by the activity of the adrenal cortex. Accordingly, inflammation is not only merely a local response, but a hormone-controlled process.